2016
DOI: 10.26719/2016.22.6.394
|View full text |Cite
|
Sign up to set email alerts
|

Burden and associated factors for caregivers of the elderly in a developing country

Abstract: The elderly population in South Asia is growing. In Pakistan trained caregivers are scarce and culturally not acceptable. This study assessed the level of stress experienced by caregivers of the elderly and determined the association of care giving burden with different characteristics of the elderly. A cross-sectional, questionnaire based study was conducted using nonprobability purposive sampling. All consenting participants aged 60 years and above needing help with at least one activity of daily living or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…This was supported by the result of (36) in his study conducted in Brazil who mentioned the same results that two-thirds of the study caregivers were married and one third were single. This is consistent with the findings of (37) in his study conducted in Pakistan, who found that three-quarters of caregivers in their study sample were married and one-quarter were unmarried. On the other hand, the result of the study (38) conducted in Saudi Arabia, revealed that nearly three-fifths were single, and more than two-fifths were married.…”
Section: Discussionsupporting
confidence: 92%
“…This was supported by the result of (36) in his study conducted in Brazil who mentioned the same results that two-thirds of the study caregivers were married and one third were single. This is consistent with the findings of (37) in his study conducted in Pakistan, who found that three-quarters of caregivers in their study sample were married and one-quarter were unmarried. On the other hand, the result of the study (38) conducted in Saudi Arabia, revealed that nearly three-fifths were single, and more than two-fifths were married.…”
Section: Discussionsupporting
confidence: 92%
“…Studies from many other countries also show that the main caregivers of the elderly were women [24][25][26][27]. Daughters-in-law were the caregivers in a significant number of households in our study, as found in studies in India [28][29][30].…”
Section: Discussionsupporting
confidence: 83%
“…This is quite high when compared with previous study of Nepal [21].This study also found elderly having functional limitations was correlated with a higher caregiving burden. Many other studies carried out in other different countries also show care given burden was highly correlated with functional limitations [28][29][30].…”
Section: Discussionmentioning
confidence: 73%
“…This finding may be explained by the fact that in low-income countries, it is taken for granted that the burden of caring for the incapacitated is mainly carried by family members and caregivers. 53,54 In high-income countries, where the proportion of the population that is older is increasing, policy makers are beginning to notice family caregivers as playing a crucial role in caring for older adults and often in making health-related decisions on their behalf. If these unremunerated caregivers are no longer able to play this role for some reason, their replacement with paid workers can pose significant problems for health care systems.…”
Section: Discussionmentioning
confidence: 99%